Programa de alimenta????o escolar de Timor-Leste: limites, desafios e possibilidades na implementa????o de uma pol??tica educacional - Boavida, Diana Viana (2016)
This work???s goal is to identify the factors that interfere in the implementation of the School Feeding Program in East Timor, the limits and its development possibilities. By the Ministry of Education???s Decree-Law 21/2006, the government established the school feeding public policy for children in basic education public schools. The FRETILIN Government, led by Dr. Jos?? Ramos Horta, launched the program in 2007. First, the program used the contingent fund from the East Timor Prime Minister???s Cabinet and received great support from an international organization called World Food Program (WFP). In 2010, the Ministry of Education takes over responsibility for the program. The field research was carried out in the Municipality of Baucau, east of East Timor. The developed research has qualitative nature and descriptive character, in a case study format. In addition to the examination of documents, 12 semistructured interviews were conducted with program managers, two representatives from the East Timor Ministry of Education ??? one national, one municipal ??? and ten directors and/or coordinators from Baucau???s basic education public schools. The research revealed that the program still has several shortcomings that prevent its implementation with quality; in addition, the program revealed a number of possibilities; the first is to contribute to the improvement of the students??? achievement in the teaching-learning process, to reduce the school drop-out rates and to increase students??? enrolment rates; it enables the inclusion of small livestock industries and small-scale local farmers and also consolidates the democratic management.